INSIDE THE CREDIT ENGINE: THE MODERATING ROLE OF CAPITAL ADEQUACY RATIO ON THE EFFECTS OF INTERNAL AND MACROECONOMIC FACTORS ON BANK CREDIT DISTRIBUTION DECISIONS - Danancy; Sunarta, I Nyoman (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to analyze the effect of Non-Performing Loans (NPL) and inflation rate on credit distribution decisions, with Capital Adequacy Ratio (CAR) serving as a moderating variable. The study focuses on the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Credit distribution represents a core function of the banking industry, which is heavily influenced by internal financial conditions and external macroeconomic factors. Fluctuations in profitability, asset quality, capital strength, and inflationary pressure play a crucial role in determining the banking sector’s capacity to extend credit to businesses and households. This research adopts a quantitative approach using secondary data obtained from the annual financial statements of conventional banks listed on the IDX between 2022 and 2024. The sample consists of 37 banks selected through a purposive sampling method. Data were analyzed using panel data regression to examine both the partial and simultaneous effects of each independent variable on credit distribution decisions. The study is theoretically grounded in Herbert A. Simon’s (1960) Decision-Making Theory and the Financial Intermediation Theory developed by Gurley and Shaw (1956). These frameworks explain how banks make lending decisions by balancing internal performance indicators, risk management, and macroeconomic conditions. The findings are expected to contribute theoretically to the development of these two theories and provide practical insights for bank management in formulating effective, data-driven credit policies. Furthermore, the study has implications for regulators in maintaining financial system stability through credit policies that account for both internal bank performance and broader macroeconomic dynamics.